Archival Appraisal: A Status Report - Couture, Carol (Archivaria, 2005)
Appraisal is one of the most significant aspects of contemporary archival science: it is its “noble function,” its central core. The author defines appraisal as “the act of judging the primary and secondary value of records and establishing the length of time during which they retain this value, within a context that respects the essential link between a given institution (or person) and the records they created in the course of their activities.” He then presents a comprehensive review of appraisal, defines the related issues and the place it occupies within the archival mission, and proposes five principles that govern the appraisal process. The author concludes by affirming that solid theoretical foundations exist to support records appraisal. RÉSUMÉ L’évaluation est une des spécificités les plus marquantes de l’archivistique contemporaine : elle en est la fonction noble et le nœud dur. Après l’avoir défini comme étant « l’acte de juger des valeurs que présentent les documents d’archives (valeur primaire et valeur secondaire) et de décider des périodes de temps pendant lesquelles ces valeurs s’appliquent auxdits documents dans un contexte qui tient compte du lien essentiel existant entre l’organisme (ou la personne) concerné et les documents d’archives qu’il (elle) génère dans le cadre de ses activités », l’auteur présente un état de la question de l’évaluation, en pose la problématique, la situe dans la mission de l’archiviste et propose cinq principes pouvant régir l’acte d’évaluer. Il soutient, en conclusion, qu’il existe une base théorique valable pour fonder l’évaluation en archivistique.